Symposium 10: Social technologies in higher education: Authorship, subjectivity and temporality - Land, Ray; Bayne, Siân (Proceedings of the International Conference on Networked Learning, 2008)
The last two decades have witnessed, as part of the wider phenomena of globalisation and supercomplexity, an inexorable shift in higher education from print-based culture to digital. This growing emphasis in the modality of learning has occasioned different ways of generating and engaging with knowledge. Whereas print culture operates from and reinforces authority (and the author), the digital works more from collaborative enquiry, consensus and trust. The volatile modes of online interaction characterised as ’Web 2.0’often sit uncomfortably within existing higher education practice. The communicative landscapes opened up by social media can be spaces of strangeness and troublesomeness to the academy, both epistemologically and ontologically (Barnett 2005). They entail a shift toward new, often ludic forms of textual mediation and subject formation. They alter relations between process and artefact, permit fragmentation over cohesion, exploration over exposition, the visual over the textual and, perhaps, convenience over quality. They are characterised by endless re-crafting, often involving rapid patterns of amendment, truncation, revision and addition. Our empirical observations of students working in such digital environments, and specifically writing within wikis and blogs, provided an interesting re-thinking of the nature of authorship. Print and digital cultures seem to favour distinctive temporalities. Whereas print culture and the cloistered academy required ’slow time’(Eriksen 2001) and private space to foster contemplation and deliberation, the digital would seem to thrive, in the main, on ’fast time’, immediacy of response, and universal virtual space. Fast time, according to Eriksen’s principles, drives out slow time. Despite unquestioned benefits of speed, there rise potential threats from fast time to reflection, creativity and to the academic estate. The contemplative space becomes dis-placed to the domestic sphere, where it is compromised anew by the digital. The notion of anti-structure, taken from the anthropological work of Turner (1969) would account for the counter-cultural quality of much Web 2.0 type activity and clarify its ’contrapuntal’position vis-à-vis the formal systemic practices of higher education. In keeping with anti-structural behaviours in other social and cultural settings, this perspective would also point to the eventual re-absorption and appropriation of Web 2.0 technologies by the formal system, before further anti-structural activities of a different nature would be likely to emerge. On the other hand Giddens’concept of distanciation would imply that Web 2.0 technologies ’stretch’the existing infrastructure across the time-space continuum to permit learners to access the existing higher education infrastructure regardless of their embodied presence along the space-time continuum. The important question arises, from a learning perspective, of whether the space of liminality (Meyer and Land 2006) the transformative threshold space and process in which (necessarily) troublesome knowledge is negotiated and conceptual difficulty encountered and overcome is truncated by fast time and the linear, consumptive’university it ushers in. Social media continue therefore to ask us to engage with a new research agenda. To what extent do the new media challenge our conventional understandings of the way in which knowledge is generated and disseminated within the academy, and to what extent to they challenge or mesh with the changing idea of the university in the age of the digital? Do students possess the forms of ’technoliteracy’(Kahn and Kelner 2005) required to manage and produce academic knowledge within such spaces? How can organisational frameworks devised for assessing conventionally-written assignments - currently operating through assessment regimes which remain largely locked in transmissive mode - be re-crafted for the open, collaborative, volatile textual spaces of the read/write web? What kinds of ’digital pedagogies’work in these spaces, and how are they perceived and experienced by students?